Baseline characterization of dengue epidemiology in Yogyakarta City, Indonesia, before a randomized controlled trial of wolbachia for arboviral disease control - Indriani, C; Ahmad, RA; Wiratama, BS; Arguni, E; Supriyati, E; Sasmono, RT; Kisworini, FY; Ryan, PA; O'Neill, SL; Simmons, CP; Utarini, A; Anders, KL (American Society of Tropical Medicine and Hygiene, 2018)
Dengue is endemic in Indonesia. Here, we describe the epidemiology of dengue in the city of Yogyakarta, Central Java, as a prelude to implementation of a cluster-randomized trial of Wolbachia for the biocontrol of arboviral transmission. Surveillance records from 2006 to 2016 demonstrate seasonal oscillations of dengue incidence with varying magnitude. Two lines of evidence demonstrate a high force of infection; the hospitalized case burden of patients diagnosed with dengue hemorrhagic fever or dengue shock syndrome over the last decade consisted predominantly of children/adolescents, and a serosurvey of 314 healthy children aged 1-10 years found 68% possessed dengue virus-neutralizing antibodies. Finally, a mobility survey indicated children aged 1-10 years, and particularly 1-5 year-olds, spent most of their daytime hours at home. These findings inform the design of clinical trials to measure the impact of novel vector control methods such as Wolbachia introgression into Aedes aegypti mosquitoes, by providing baseline data on disease incidence and identifying subpopulations for recruitment into prospective studies of dengue virus infection and disease. The mobility survey findings indicate that in cluster trials of interventions applied at the community level, young children can reasonably be expected to spend most of their exposure time, in epidemiological terms, within the treatment arm to which they were randomized.